2022
DOI: 10.3390/app12052466
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Speed of Airflow in a Cleanroom on the Degree of Air Pollution

Abstract: The high-energy requirements of cleanrooms are the main motivation for optimizing their operational conditions. The ventilation system consumes the most energy in order to ensure the precise air conditioning of the room (filtration, temperature, and humidity adjustment). The main function of the ventilation system is to keep particle concentration to a minimum. This work deals with the optimization of an experimental operating room via the optimization of air supply through the distribution element (laminar ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…The results of this study support that outcome, as the BFPC results correlate well with particles and may also be used to continuously control the bioburden status of a cleanroom with early warning possibilities in case of high microbial values. This is in line with the study results of Mičko et al [11], who found that 'lower flow rates reduce unwanted turbulence and the magnitude of velocity fluctuations, making the ventilation system more efficient at removing contaminants . .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study support that outcome, as the BFPC results correlate well with particles and may also be used to continuously control the bioburden status of a cleanroom with early warning possibilities in case of high microbial values. This is in line with the study results of Mičko et al [11], who found that 'lower flow rates reduce unwanted turbulence and the magnitude of velocity fluctuations, making the ventilation system more efficient at removing contaminants . .…”
Section: Discussionsupporting
confidence: 90%
“…Energy savings by means of reduced ACRs has been described by various authors [6,11,37]. In a previous publication by Behrens et al [10], which focused on a regulatory limit values for particles >0.5 µm and >5 µm, it was stated that ISO 8 cleanroom operations can be performed with lower ACRs than 20 h −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mičko, P. et al [17] studied the effect of air pollution on the airflow rate in a clean room. Velocity and particle trajectories were investigated using Ansys Fluent and subsequently validated using the PIV method.…”
Section: Introduction Of Latest Technologies and Researchmentioning
confidence: 99%